(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
In this study was impact of ozone treatment efficiency of wheat quality (physical-chemical and microbiological parameters, chemical composition and germination rate) during storage analysed. Ozone is a powerful oxidizer, used in processing the agricultural products, including inactivation of pathogens and microorganisms.Investigations in the grain storage by using ozone were performed under farm conditions during two grain storage stages. The first stage – August 2019 – February 2020 and the second stage August 2020 – January 2021. In both stages after harvesting winter wheat yield was 6 t ha-1. Winter wheat was ventilated and then stored for about five months in two identical 20 m3 tanks, with an initial grain layer height of 5.1 m and moisture content the first stage of about 14% and the second stage of about 11% and initial grain mass 17.4 t.At the beginning of the storage period the grain in both tanks was ventilated for 8 hours - in one grain storage tank with the outdoor air, in the other with an ozone supply of 28 mg (m3)-1 in the ventilation air. The grain ventilation and storage process was monitored with a specially designed sensor system; the additional parameters of the process (the grain moisture content, temperature, the ozone concentration) were periodically controlled with hand tools. There were analysed changes of the grain parameters during the storage periods in the ozone-supplied tank and in the tank without ozone treatment.The microbiological contamination during storage did not exceed the allowed level; however it was lower in the ozone treated wheat grain than in the ozone untreated grain. The ozone treatment did not affect the grain quality parameters. The grain germination rate for 3 and 5 days of the ozone treated grain was about 20% higher than that of the untreated grain. During storage, microbiological contamination did not exceed the permissible level, but ozone treated grains were lower than those of untreated, grain quality indicators were not affected by ozone treatment, germination of ozone treated grains was about 20% higher than untreated, baking properties were not affected by ozone treatment. The treatment of grain with ozone makes stored grain more expensive approximately 5.00 EUR per ton, due to additional technical equipment required to ensure the ozone treatment process. One can conclude from the attained results that processing the restored grain under the conditions mentioned reduces the grain microbiological contamination; it does not affect the grain quality parameters and baking properties; it slightly improves the grain germination rate and has no impact upon the shell of the grain.